The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2147/ijn.s33584
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite nanoparticles inhibit the growth of human glioma cells in vitro and in vivo

Abstract: Hydroxyapatite nanoparticles (nano-HAPs) have been reported to exhibit antitumor effects on various human cancers, but the effects of nano-HAPs on human glioma cells remain unclear. The aim of this study was to explore the inhibitory effect of nano-HAPs on the growth of human glioma U251 and SHG44 cells in vitro and in vivo. Nano-HAPs could inhibit the growth of U251 and SHG44 cells in a dose-and time-dependent manner, according to methyl thiazoletetrazolium assay and flow cytometry. Treated with 120 mg/L and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 28 publications
2
66
0
1
Order By: Relevance
“…Razvojem nanotehnologije, pokazano je da nHAp-a inhibiraju proliferaciju ćelija različitih vrsta tumora, ali njihov uticaj na ljudske ćelije glioma nije dovoljno istražen. U cilju postavljanja teorijskih osnova za kliničku upotrebu ispitivan je inhibitorni efekat nHAp-a na rast ljudskih ćelija glioma (U251 i SHG44), pri čemu je pokazano da nHAp indukuje apoptozu tumorskih ćelija glioma in vitro i in vivo, a u kombinaciji sa hemoterapeutskim medikamentom: BCNU (1,3-bis(2-chloroethyl)-1-nitrosourea) značajno smanjuje nuspojave [74].…”
Section: Sinteza I Dizajniranje Multifunkci-unclassified
“…Razvojem nanotehnologije, pokazano je da nHAp-a inhibiraju proliferaciju ćelija različitih vrsta tumora, ali njihov uticaj na ljudske ćelije glioma nije dovoljno istražen. U cilju postavljanja teorijskih osnova za kliničku upotrebu ispitivan je inhibitorni efekat nHAp-a na rast ljudskih ćelija glioma (U251 i SHG44), pri čemu je pokazano da nHAp indukuje apoptozu tumorskih ćelija glioma in vitro i in vivo, a u kombinaciji sa hemoterapeutskim medikamentom: BCNU (1,3-bis(2-chloroethyl)-1-nitrosourea) značajno smanjuje nuspojave [74].…”
Section: Sinteza I Dizajniranje Multifunkci-unclassified
“…nHA with the size of >100nm has been developed over the past years. Several groups have shown that nHA NPs have minimal effects on healthy cells whilst at the same time inhibit specifically the cellular proliferation of cancer cells, such as liver and glioma cells [52][53][54]. nHA NPs coated with a fluorescent dye are great carriers for applications such as imaging or for photodynamic therapy.…”
Section: Nano-hydroxyapatite (N-ha)mentioning
confidence: 99%
“…The nanoparticle form of calcium phosphate has antiproliferative and pro-apoptotic effects on glioma [176] and osteosarcoma [54] cells. Similarly, their homeopathically-manufactured counterparts, e.g., Ruta graveolens 6C and Calcarea Phosphorica 3X [172], are part of a leading combination anti-cancer protocol for gliomas [108,172].…”
Section: Experimental Questionsmentioning
confidence: 99%
“…The diagnosisbased selection of medicines facilitates providing care from a public health perspective to a large number of patients. Bulk herb extracts of Ruta graveolens, for instance, exert anti-cancer effects [173,174]; and an oral nanoscale formulation of one of its main constituents, rutin, has good bioavailability [175].The nanoparticle form of calcium phosphate has antiproliferative and pro-apoptotic effects on glioma [176] and osteosarcoma [54] cells. Similarly, their homeopathically-manufactured counterparts, e.g., Ruta graveolens 6C and Calcarea Phosphorica 3X [172], are part of a leading combination anti-cancer protocol for gliomas [108,172].…”
mentioning
confidence: 99%